Chemical measurements in biological systems - Stewart, Kent K. (John Wiley, 2000)
Techniques in Analytical Chemistry. How to evaluate and validate data from chemical measurements in biological systems-a unique overview. An understanding of chemical measurement processes in biological systems is essential to working in today's life-science and biotechnology industries. This work provides analysts and laboratory professionals with the fundamental knowledge and basic principles they need to tackle the measurement process in the real world. Rather than rehashing traditional analytical techniques, which can be problematic for biological samples, the book emphasizes the highly complex nature of biological systems through such topics as enzyme measurements, enzymes as reagents, immunochemical assays, and assay validation and quality control. It provides a complete overview of principles and methods proven useful in biological systems-from pH, buffers, and spectrophotometry to basic chromatographic techniques. With Chemical Measurements in Biological Systems as their guide, readers will understand the basic principles needed to: * Read and evaluate an assay method description * Choose the appropriate method from the vast array of available techniques * Modify and evaluate an existing method for specific needs * Set up and run biochemical assays * Use multistep problem-solving techniques * Evaluate the results of a given assay in a given matrix